Wheel Slip Control of Vehicle ABS Using Piezoactuator-Based Valve System. (6th April 2014) - Jeon, Juncheol; Choi, Seung-Bok; Lee, Yang-Sub
Abstract : This paper presents a novel piezoactuator-based valve for vehicle ABS. The piezoactuator located in one side of a rigid beam makes a displacement required to control the pressure at a flapper-nozzle of the pneumatic valve. In order to obtain the wide control range of the pressure, a pressure modulator comprised of dual-type cylinder and piston is proposed. The governing equation of the piezovalve system which consists of the proposed piezoactuator-based valve and the pressure modulator is obtained. The longitudinal vehicle dynamics and the wheel slip condition are then formulated. In order to evaluate the performance of the proposed piezovalve system from the viewpoint of the vehicle ABS, a sliding mode controller is designed for wheel slip control. The tracking control performances for the desired wheel slip rate are evaluated and the braking performances in terms of braking distance are then presented on different road conditions (dry asphalt, wet asphalt, and wet jennite). It is clearly shown that the desired wheel slip rate is well achieved and the braking distance and braking time can be significantly reduced by using the proposed piezovalve system associated with the slip rate controller.